2001
DOI: 10.1067/mcp.2001.114667
|View full text |Cite
|
Sign up to set email alerts
|

The endothelin antagonist bosentan inhibits the canalicular bile salt export pump: A potential mechanism for hepatic adverse reactions

Abstract: These results indicate that bosentan-induced liver injury is mediated, at least in part, by inhibition of Bsep/BSEP-causing intracellular accumulation of cytotoxic bile salts and bile salt induced liver cell damage. The data further emphasize the pathophysiologic importance of drug-Bsep interactions in acquired forms of cholestatic liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
369
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(389 citation statements)
references
References 29 publications
14
369
0
6
Order By: Relevance
“…The same drugs also inhibit human BSEP [9,72]. Other drugs that have been shown to inhibit BSEP are bosentan [25], troglitazone [29], and fluvastatin (C. Lang, Y. Meier, and C. Pauli-Magnus, submitted for publication). Such drugs may, in susceptible humans, cause acquired cholestasis, which rapidly resolves after the withdrawal of the drug.…”
Section: Pathophysiological Consequences Of Altered Bsep Function Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The same drugs also inhibit human BSEP [9,72]. Other drugs that have been shown to inhibit BSEP are bosentan [25], troglitazone [29], and fluvastatin (C. Lang, Y. Meier, and C. Pauli-Magnus, submitted for publication). Such drugs may, in susceptible humans, cause acquired cholestasis, which rapidly resolves after the withdrawal of the drug.…”
Section: Pathophysiological Consequences Of Altered Bsep Function Andmentioning
confidence: 99%
“…This canalicular hypercholeresis may lower the bile salt concentration in the canalicular lumen and consequently reduce canalicular lipid secretion [28]. Such a mechanism could in turn lead, via secondary inhibition of Bsep, to the observed accumulation of serum bile acids in rats after administration of bosentan [25,60]. Studies with mouse Bsep demonstrated that some drugs inhibit not only the transport activity of Bsep but also its ATPase activity [69].…”
Section: Pathophysiological Consequences Of Altered Bsep Function Andmentioning
confidence: 99%
“…Covalent adduct formation, immunotoxicity, and disruption of cellular bioenergetics have been considered previously as mechanisms underlying hepatotoxicity, but more recent data suggest that hepatic transport proteins may be an important site of toxic interactions (Fattinger et al, 2001;Funk et al, 2001;Leslie et al, 2007). The objective of this study was to evaluate the capability of sandwich-cultured primary rat hepatocytes (SCRH), which more closely mimic the metabolic and transport capabilities of the intact liver, to predict the hepato-protective effect of DEX against trabectedin-mediated hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common side-effects associated with ERA therapy is hepatotoxicity, usually detected by an increase in the serum aminotransferases [1,4]. The underlying mechanism may be related to inhibition of a bile-salt transporter pump [5]. The typical pattern of this type of liver injury is that of a toxic mechanism, i.e.…”
mentioning
confidence: 99%